Threshold of Hearing and Magnitude of Acoustic Reflex in Children - Kamini R (Journal of All India Institute of Speech and Hearing, 1970)
Early identification of hearing loss in children is very importanat for fruitful rehabilitation. Accurate assessment of hearing according  to Lamb(1975), is often hindered by the inability or unwillingness of the subject to respond to sound in a prescribed manner. Children constitute a major portion of such  difficult-to- test (Fulton and Lloyd, 1975) population.